Effect of deacetylation degrees variation on chitosan nerve conduit for peripheral nerve regeneration - Qulub, Fitriyatul; Widiyanti, Prihartini; Maulida, Hendita Nur; Indrio, Ludita Woro; Wijayanti, Tia Rahayu (Folia Medica Indonesiana, 2017)
Broken nerves could regenerate when exposed to simple injuries by using a nerve conduit that has appropriate physiological and mechanical ability to support the nerves regeneration around the fissure of trauma. One of the biopolymer for the conduit composition is chitosan because it is biocompatible, biodegradable, non-toxic, and has similarity structure as natural glycosaminoglycans. The aim of research is to synthesize chitosan with variation of Degrees of Deacetylation (DD) and characterize the DD influence on mechanical properties and biocompatibility. Research design is prospective observational. Chitosan was treated with a decrease in the DD method and an increase in the temperature with the strength of alkaline solution, which was NaOH solution with concentrations of 5%, 20%, 35%, and 50% within 2 hours with a heating temperature of 95°C. The results of each DD variation were 23.24, 46.55, 53.48, and 55.06. It was characterized by tensile test with tensile strength values of 0.25 - 1.18 MPa. The degradation test results tend to decrease with the increasing concentration of NaOH proving that samples are biodegradable. The surface morphology of samples shows a pore range of 61.52 Î¼m - 220.3 Î¼m. The best result is the chitosan sample with 35% NaOH because due to the tensile characteristic and a pore in accordance with normal standard. Tensile strength is around 0.41 MPa - 3.69 MPa and pore size around 40 Î¼m – 250 Î¼m to accelerate nerve regeneration. The results are expected to provide alternative solution of nerve conduit development for peripheral nerve defects.